Perceived Behavior Model for Heart Disease Prevention in BPJS Mandiri Participants: A Health Belief Approach - Yeni Riza; Wasis Budiarto; Setya Haksama; Kuntoro Kuntoro; Ririh Yudhastuti; Arief Wibowo; Hari Basuki Notobroto; Fitri Rachmillah Fadmi (Health Dynamics, 2025)
Background: Heart disease remains a leading cause of death globally and is increasingly prevalent in Indonesia. Preventive behavior plays a crucial role in reducing the burden of this disease, especially among populations with limited healthcare access. This study aims to develop a Perceived Behavior Model based on the Health Belief Model combined with WHO's STEPWise approach to enhance health quality related to heart disease prevention behaviors. Methods: This observational cross-sectional study examined demographic factors, perceived susceptibility, seriousness, barriers, benefits, self-efficacy, and cues to action regarding heart disease preventive behavior. Participants adopted preventive measures such as maintaining a healthy diet, refraining from smoking, avoiding alcohol consumption, and staying physically active. The study surveyed 435 individuals from the total 82,232 BPJS Mandiri (self-paying participants of Indonesia’s National Health Insurance system) members in Banjarmasin, Indonesia, without any intervention. Data analysis was conducted using the Partial Least Square (PLS) method with SmartPLS software version 3.29. The full model of structural equation modeling and theory confirmation also examined the presence or absence of relationships between latent variables. Result: The study found a direct and positive effect of demographic factors on perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, and self-efficacy, as well as on perceived susceptibility and seriousness regarding heart disease preventive behaviour. Conclusions: Understanding these cultural influences can guide policymakers in strengthening prevention strategies within Indonesia’s Social Security Agency of Health system, reducing financial burdens, and improving public health outcomes. These insights may also inform global discussions on culturally tailored health interventions.